Answer:
(2, -8)
Step-by-step explanation:
(x, y)=(-3, -1)
(x1+x2)/2=-3,
(y2+y2)/2=-1,
-------------------
(x1+x2)/2=-3
(y1+y2)/2=-1
---------------------
x1-8=-6
x1=2
----------
y1+6=-2
y1=-8
(2, -8)
.72
18/25
Please mark brainliest
Answer: f(x) = -9x
Step-by-step explanation:
Remember that f(x) is the same thing as y.
y = 3x + 6x + 2y
First, combine like terms to get...
y = 9x + 2y
Then, subtract -2y from each side to get..
-y = 9x
Next, you divide by -1 and get...
y = -9x ,which is your answer
Hope this is helpful :)
Answer:
A. 7
Step-by-step explanation:
h(x)=2x + 4
2(7)=14
14+4=18